Analisis Koreksi Fiskal Atas Laporan Keuangan Komersial Pada PT. Aneka Tambang (Persero) Tbk Tahun 2020-2021 - Ayu, Rhea Samantha; Murti, Galuh Tresna; Mamola, A. Rendy Sandra; Rachmawati, Restika Okta (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
The largest source of state revenue comes from taxes, including Corporate Income Tax (PPh Badan) imposed on corporate income within a year. "Corporate" encompasses entities such as limited company, state-owned corporation, regional corporation, cooperatives, foundations, and others. In Indonesia, the collection system for Corporate Income Tax uses a self-assessment system, where taxpayers calculate, pay, and report their taxes independently. This system increases administrative efficiency and reduces the burden on the government but requires strict supervision to prevent tax evasion. PT Aneka Tambang Tbk 2020-2021, a mining company, was chosen as the research object to study financial and tax management. The commercial financial statements of PT Aneka Tambang 2020-2021 show discrepancies that require fiscal corrections, such as asset impairment and amortization of discounts. The analysis of fiscal corrections reveals that after the adjustments, PT Aneka Tambang's 2020-2021 taxable profit reached Rp 113,924,826, with a Corporate Income Tax due of Rp 28,481,206.5. This research highlights the importance of compliance and supervision in the self-assessment system to ensure stable and sustainable tax revenue. Through proper fiscal corrections, financial statements can be adjusted in accordance with tax regulations, ensuring that taxable profits are accurately calculated and tax obligations are met in accordance with the provisions.Â Keywords: Corporate Income Tax, Self-Assessment System, Fiscal Correction, Financial Statements, PT Aneka Tambang Tbk